WHAT MAKES INTRODUCTORY PHYSICS DIFFICULT? - Untung Nugroho Harwanto (Program Studi Matematika FMIPA Universitas Pamulang, 2019)
The purpose of this study was to make an investigation what makes physics difficult. Students from different islands in Indonesia who were taking a preparation course in South Tangerang were taken into account of survey. A yes-no answer questionnaire was prepared in order to get the students perception toward physics. The questionnaire was given to approximately 115 students in the middle of the semester. The students were asked to full fill a questionnaire through what makes introductory physics difficult. We found that factor related to the nature of physics is taking part as the maximum percentage on the reason why physics considered as a difficult subject. But factor related to the courses is taking part as the minimum percentage on the reason why physics considered as a difficult subject. The female and male students mostly agreed that the factor related to the nature of physics and took more than fifty percent. Lack of physics background, lack of previous experience and working only assigned problem have the high percentage as the part of student controlled factor. Physics is cumulative subject and physics required good mathematics both are taking high percentage related to the nature of physics.